DEVELOPING RECOUNT TEXT MATERIALS BASED ON K13 CURRICULUM FOR THE TENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL : (Study at SMAN 1 Ponggok Blitar) - Sutanti, Nita; Sari, Hesty Puspita; Karina, Galuh (Universitas Islam Balitar, 2019)
This research was aim to develop recount text materials to the tenth grader students of senior high school and find out the effectiveness of the recount text materials. This research was done in SMAN 1 Ponggok. The researcher used Research and Development (R & D) adopted from of Sugiyono’s model (2015:298) to conduct the research. The data collected through interview, questionnaire, documentation, and test. The expert validation which used in this research were; 1) media expert 2) material expert. To try out the product, the researcher used one group pre-test and post-test experimental design. The results of the research showed that the develop of Recount Text Material was effective; it proved by 1) The result of material validation 98.18% and media validation 96.25 %. The average of those two validation is 97,22% that categorized as “very good” by interval 80% < x ≤ 100%. So, the supplementary book of Recount text Material which developed was valid to be implemented in the tenth grader of Senior high school students. 2) It also increase the tenth grade students’ writing achievement that proved by the increase of the students’ of pre test mean score (66.67) to post test mean score (83.83). 3) The students also gave positive responses toward Recount Text Material as reflected from the result of the questionnaire given (85.8%). From that result presented before, it can be concluded that Recount Text Material was effective and increased the tenth grade students’ writing achievement. It means Recount Text Material can be used as a supplementary media for learning English writing.